(untitled) (Journal of Health, Population and Nutrition, 2011)
When compared with Thailand, the seroprevalence of hepatitis A virus (HAV) is extremely high among its neighbouring countries. To investigate the seroprevalence of HAV among the Thai people residing in the border area between Thailand and Myanmar, 308 residents in Umphang, Maesod district, Tak, were recruited. Sera were tested for HAV IgG antibodies by enzyme-linked immunosorbent assay. The overall seroprevalence among the Thai people residing in the border area of Thailand was significantly higher than that among the general Thai population (71% vs 27% respectively, p<0.05). As asymptomatic or mild HAV infection typically occurs in children, the Thai people residing in the border area may receive little benefit from universal HAV vaccination. Lower protective antibodies against HAV, along with the exclusion of HAV vaccine from the Expanded Programme on Immunization, potentially increase the susceptibility to HAV among the general Thai population and may lead to more future outbreaks if HAV is introduced from the border areas. The findings suggest that HAV vaccines should be recommended to travellers before their journey to the border between Thailand and Myanmar where HAV is endemic. Key words: Hepatitis A; Seroprevalence; Myanmar; Thailand DOI: http://dx.doi.org/10.3329/jhpn.v29i2.7861 J HEALTH POPUL NUTR 2011 Apr;29(2):174-177